Opening and Closure of the Sulu Sea: Revealed by Its Peripheral Subduction and Collision Processes - Yunliu Yang; Xinong Xie; Yunlong He; Hao Chen (Journal of Marine Science and Engineering, 2024)
The Sulu Sea is a small marginal sea in the western Pacific, but it is a very complex and tectonically active region, situated amidst the convergence of the Eurasian, Pacific, and India-Australian plates. Deciphering its geodynamic evolution is crucial, but our understanding of its opening, closure, and tectonic history remains inadequate. The main aim of this study was to systematically study the opening and subsequent closure of the Sulu Sea though discerning tectonic unconformities, structural features, and subduction-collision tectonic zones around margins of the sea. The interpreted sections and gravity anomaly data indicate that the NE Sulu Sea has undergone Neogene extension and contraction due to subduction and collision along the northern margins of the Sulu Sea, whereas the SE Sulu Sea gradually extended from northwest to southeast during the Middle Miocene and has subsequently subducted since the Middle Miocene along the southeastern margins of the Sulu Sea. Several subduction and collision boundaries with different characteristics were developed including continent-continent collision, arc-continent collision, and ocean-arc subduction. The different margins of the Sulu Sea showed distinct asynchronous subduction and collision processes. The northern margins of the Sulu Sea can be divided into three subduction-collision tectonic zones from west to east: the Sabah-Nansha block collision has occurred in NE Borneo since the Early Miocene, followed by the SW Palawan-Cagayan arc collision in SW Palawan Island since the Middle Miocene, and the NW Palawan-Mindoro arc collision since the Late Miocene with further oblique subduction of the Philippine Sea Plate. The southeastern margins can also be divided into two subduction tectonic zones from south to east: the SE Sulu Sea has subducted southward beneath the Celebes Sea since the Middle Miocene, followed by the southeastward subduction beneath the Philippine Sea Plate since the Pliocene. Since the Miocene, the interactions among the Australia-India, the Philippine Sea, and the Eurasian plates have formed the circum-Sulu Sea subduction-collisional margins characterized by microplate collisions, deep-sea trough development, and thick sediments filling in the orogenic foreland. This study is significant for gaining insights into the opening and closure of marginal seas and the dynamics of multiple microplates in Southeast Asia.